O Exultet como expressão dos sentimentos de um povo redimido - Pereira, Jerônimo (Revista Eclesiástica Brasileira, 2019)
A primeira parte da Vigília Pascal encontra seu ponto culminante no canto diaconal do Exultet. O presente artigo tem como escopo apresentar, de forma sintética, os elementos do affectus fidei da Igreja redimida, presentes no lirismo da narração melódico-textual expressa pelo diácono. Parte-se da análise antropológica dos sentimentos humanos e de sua dimensão intersubjetiva; apresenta-se o contexto histórico e litúrgico do Exultet e, finalmente, analisam-se as expressões dos sentimentos. Os resultados, mesmo que sumários, evidenciam, sobretudo, a importância da lex orandi na transmissão-expressão da fé/salvação experimentada per ritus et preces. Abstract: The first part of the Easter Vigil has its climax in the diaconal chanting of the Exultet. The objective of the present article is to present, in a synthetic form, the elements of the affectus fidei of the redeemed Church, present in the lyricism of the melodic-textual narration expressed by the deacon. We begin with the anthropological analysis of human feelings and their inter-subjective dimension; we introduce the historical and liturgical context of the Exultet and finally analyse the expression of these feelings. The results, even if summarized, make evident, clearly and above all, the importance of the lex orandi in the transmission-expression of the faith/salvation experienced per ritus and preces. Keywords: Exultet; Feelings; Liturgy; Easter Vigil; Church.